2017
DOI: 10.2134/agronj2016.03.0150
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Satellite Imagery and Ground‐Based Active Optical Sensors as Yield Predictors in Sugar Beet, Spring Wheat, Corn, and Sunflower

Abstract: Algorithms using active-optical (AO) sensors have been developed to direct in-season N application to crops. Many farmers in the United States have a large number of farm fi elds to manage. Farmers using AO technology must visit each fi eld and operate the sensor across the entire fi eld in order to conduct in-season N application. A fi eld might be driven over with an on-the-go N fertilizer applicator, but the application might not be required. Th e objective of this study was to determine whether satellite i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 42 publications
1
29
1
1
Order By: Relevance
“…We suggest that while developing P recommendations, it may be essential to differentiate between soil types and regions. For example, in North Dakota, United States for N in corn, sunflower, and wheat [53][54][55][56][57][58][59][60][61] recommendations were developed considering soil variability, the price of the commodity, cultivation system, yield potential, and soil moisture. It was found that there is a need to examine banded application according to the crop root system development because banded application P stays where it is applied.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that while developing P recommendations, it may be essential to differentiate between soil types and regions. For example, in North Dakota, United States for N in corn, sunflower, and wheat [53][54][55][56][57][58][59][60][61] recommendations were developed considering soil variability, the price of the commodity, cultivation system, yield potential, and soil moisture. It was found that there is a need to examine banded application according to the crop root system development because banded application P stays where it is applied.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in slope within a landscape can have a substantial impact on grain yield variability [64]. Soil depth and drainage also have a significant impact on corn grain and potato yield [65]. In commercial crop production, higher N fertility levels have been observed in foot slopes and depressions due to the flow of water and soil deposition of clay and organic matter to these landscape positions.…”
Section: Spatial Variationmentioning
confidence: 99%
“…This indicates that estimation of yield and potential for N response in relative terms is possible. Several studies were conducted to improve the relationship between crop yield and sensor readings [65,106,107,[131][132][133], however, their practical application is still in question due to their inconsistent results.…”
Section: Use Of Sensors and Ndvimentioning
confidence: 99%
See 1 more Smart Citation
“…2018, 10, 68 8 of 20 this study include the NDVI and an NDVI combined with the NIR reflectance of vegetation (NIRv). The NDVI is a key parameter that is used to improve the accuracy of yield prediction for sugar beets, spring wheat, corn, and sunflower based on the NDVI relationships with optical signals under different nitrogen (N) and sulfur (S) contents [68][69][70][71][72][73][74][75][76]. Notably, the NDVI has been widely used for LAI extraction from high spatial resolution imagery [21,22,24,25,29,77].…”
Section: Lai Inversion Proceduresmentioning
confidence: 99%